Production of Liquid Soap from Virgin Coconut Oil with the Active Ingredient Citronella Oil (Sainteknol : Jurnal Sains dan Teknologi, 2023)
The use of hand-washing soap is able to kill germs because it can remove oil and dirt that sticks to the hands. In making this liquid soap, active substances from nature, which is citronella oil, are used as anti-bacterial and anti-fungal agents. This study aims to study the factors that influence the response of free alkali and optimum conditions in the manufacture of liquid soap. The optimization method uses Response Surface Methodology (RSM) based on Central Composite Design. Experimental variables were carried out at reaction temperature (60-80°C), KOH concentration (30-50%), and reaction time (30-50 minutes). The results of the analysis using statistical software obtained the optimum operating conditions for the reaction time of 56,818 minutes, KOH concentration of 46,818%, and reaction temperature of 86,818°C with a free alkali value response of 0.04158%. These results meet the SNI 06-4085-1996 standard with a free alkali value below 0.1%.